Laparoscopic evaluation of tubal pathology in cases of infertility (Ibrahim Medical College Journal, 2014)
Infertility is a public health problem in developed and developing countries. Diagnostic laparoscopy is a generally accepted procedure to detect pelvic organ pathologies affecting fertility. This study was undertaken to find out the tubal pathology contributing to primary and secondary infertility by laparoscopic examination. The study was carried out in the department of Gynaecology and Obstetrics, BIRDEM during the period of January 2001 to December 2001. The study group comprised of 100 cases of infertile patients of age between 20 to 40 years. Sixty seven percent patients had primary infertility and 33% patients had secondary infertility. Size and shape of the uterus was normal in 69% cases and bicornuate uterus was found in 2% cases. Out of total cases, 71% and 69% had normal right and left fallopian tubes respectively. Patency of right and left fallopian tube was normal in 90% and 89% cases respectively while 11% and 10% had peritubal adhesions. Laparoscopy examination is an important tool for evaluation of tubal pathology contributing to infertility and might play a major role in infertility management. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20110 Ibrahim Med. Coll. J. 2013; 7(2): 38-40